2022
DOI: 10.1002/brb3.2679
|View full text |Cite
|
Sign up to set email alerts
|

Grey matter atrophy in patients with benign multiple sclerosis

Abstract: Background: Brain atrophy appears during the progression of multiple sclerosis (MS) and is associated with the disability caused by the disease. Methods:We investigated global and regional grey matter (GM) and white matter (WM) volumes, WM lesion load, and corpus callosum index (CCI), in benign relapsingremitting MS (BRRMS, n = 35) with and without any treatment and compared those to aggressive relapsing-remitting MS (ARRMS, n = 46). Structures were analyzed by using an automated MRI quantification tool (cN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 63 publications
(95 reference statements)
0
3
0
Order By: Relevance
“…Location, unique functions, and vulnerability to MS neuropathology from the earliest disease stages render the thalamus a critical barometer of diffuse neuropathologic damage in MS patients 18 . To date, thalamic atrophy has been associated with the evolution of de nite MS and disability progression in early RRMS patients and with the evolution of PPMS [23][24][25] . Therefore, our results were basically in accordance with these previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…Location, unique functions, and vulnerability to MS neuropathology from the earliest disease stages render the thalamus a critical barometer of diffuse neuropathologic damage in MS patients 18 . To date, thalamic atrophy has been associated with the evolution of de nite MS and disability progression in early RRMS patients and with the evolution of PPMS [23][24][25] . Therefore, our results were basically in accordance with these previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…Benign multiple sclerosis (MS) pertains to a certain subset of individuals diagnosed with MS, commonly characterized by relapsing-remitting MS (RRMS), who manifest relatively mild symptoms and demonstrate limited progression of disability over a prolonged duration. (75,76) Clinically Isolated Syndrome (CIS) is distinguished by a singular clinical occurrence of neurological symptoms that suggest a possible connection with Multiple Sclerosis (MS), as opposed to being categorized as a separate subtype of the condition (77). Some individuals who have been diagnosed with clinically isolated syndrome (CIS) may experience a progression leading to the development of multiple sclerosis (MS) (78).…”
Section: Clinical Manifestations and Disease Subtypesmentioning
confidence: 99%
“…In this direction, Golan et al [43] found that computerized cognitive scores were significantly associated with quantified MRI. Additionally, Niiranen et al [44] identified grey matter volume as a significant measure for distinguishing between EDSS-based BMS and non-BMS cases. To summarize, there is still no general agreement for the definition for BMS, but active research is being conducted toward an updated definition which covers a fuller spectrum of MS disease activity.…”
Section: Rf-phate Provides Insights Into Benign Msmentioning
confidence: 99%